An adaptive planning strategy in carbon ion therapy of pancreatic cancer involving beam angle selection. (January 2022) - Kawashima, Motohiro; Tashiro, Mutsumi; Varnava, Maria; Shiba, Shintaro; Matsui, Toshiaki; Okazaki, Shohei; Li, Yang; Komatsu, Shuichiro; Kawamura, Hidemasa; Okamoto, Masahiko; Ohno, Tatsuya
Highlights: In this study, we proposed a new adaptive strategy. A new option in treatment planning for particle therapy was considered. The high dose region for OARs was similar for the proposed and conventional strategies. The objective was to improve target coverage of the accumulated dose distribution. Abstract: Background and purpose: In carbon-ion radiotherapy for pancreatic cancer, altered dose distributions due to changes in the gastrointestinal gas volume and anatomy during irradiation are an unresolved therapeutic issue. We developed and investigated an adaptive strategy involving beam angle selection to improve dose distributions in pancreatic cancer. Materials and methods: In the adaptive strategy, multiple beams were prepared with angles similar to those of the conventional strategy, and the beam that best reproduces the dose distribution of the treatment plan was used. The dose distributions of the adaptive strategy were compared with those of the conventional strategy for five patients. Patients underwent computed tomography (CT) before every irradiation. The adaptive strategy was evaluated using the same irradiation schedule as that of the conventional method and an adjusted method based on anatomical changes per fraction. Dose distributions on the pre-treatment CT and accumulated dose distributions on the treatment planning CT were evaluated using the volume receiving ≥95% of the prescription dose (V95) from the clinical target volume (CTV) between strategies. Results: There were significant differences in the CTV V95 values for the pre-treatment CT between all strategies. The median (range) CTV V95 for the conventional strategy was 92.7% (87.1–96.1%), for the proposed adaptive strategy without adjusted schedules was 96.9% (95.1–97.8%), and for the proposed strategy with adjusted schedules was 97.8% (96.5–99.2%). Conclusions: The adaptive strategy can improve target coverage for the pre-treatment CT and accumulated dose distributions for the treatment planning CT without increasing the dose to critical organs.